(untitled) (Revista Apotheke, 2020)
This paper starts from the provocations of Fischer and Loponte (2020) regarding the ways of inhabiting the school, and from their invitation to look at the school for what is possible to invent and create in it. In this context, it engages in dialogue with authors such as Masschelein, Simons; Helguera; Bosi; Vergara; Irwin, to reflect on the Place of Memory and Art, a project linked to the PIBID project at the Federal University of Juiz de Fora (State of Minas Gerais, Brazil) that suggested a series of propositions of fruition and artistic creation with students from the second cycle of elementary school in a public school in the city of Juiz de Fora, State of Minas Gerais (Brazil). The project promoted exchanges of experiences between these students and invited artists, which made it possible to inhabit a museum with works created at the school by the participants of the meetings, thus revealing a school that invents and occupies spaces.